Activity-dependent axonal plasticity in sensory systems - Jamann, Nora; Jordan, Merryn; Engelhardt, Maren (Neuroscience, 2018)
The rodent whisker-to-barrel cortex pathway is a classic model to study the effects of sensory experience and deprivation on neuronal circuit formation, not only during development but also in the adult. Decades of research have produced a vast body of evidence highlighting the fundamental role of neuronal activity (spontaneous and/or sensory-evoked) for circuit formation and function. In this context, it has become clear that neuronal adaptation and plasticity is not just a function of the neonatal brain, but persists into adulthood, especially after experience-driven modulation of network status. Mechanisms for structural remodeling of the somatodendritic or axonal domain include microscale alterations of neurites or synapses. At the same time, functional alterations at the nanoscale such as expression or activation changes of channels and receptors contribute to the modulation of intrinsic excitability or input-output relationships. However, it remains elusive how these forms of structural and functional plasticity come together to shape neuronal network formation and function. While specifically somatodendritic plasticity has been studied in great detail, the role of axonal plasticity, (e.g. at presynaptic boutons, branches or axonal microdomains), is rather poorly understood. Therefore, this review will only briefly highlight somatodendritic plasticity and instead focus on axonal plasticity. We discuss (i) the role of spontaneous and sensory-evoked plasticity during critical periods, (ii) the assembly of axonal presynaptic sites, (iii) axonal plasticity in the mature brain under baseline and sensory manipulation conditions, and finally (iv) plasticity of electrogenic axonal microdomains, namely the axon initial segment, during development and in the mature CNS.